(untitled) (Studia Prawnicze / The Legal Studies, 2023)
The article presents the problem of various forms of the material aid granted by the State to denominations in the USA — inter alia: endowing their social activity, subsidizing the faith school system, exempting the faith organizations from taxes — from the viewpoint of their consistency with the Constitution and especially in conformity upon the principle of Church and State separation. The author analyzes a respective judicature of the Supreme Court without abstracting from the social evalution caused by it. Furthermore, he widely discusses the viewpoints of the doctrine analysing them critically. This results in numerous conclusions. Among others, he tries to prove that the State material aid to the faith organizations treated as an institution is contrary to the principle of Church and State separation. However, there exist some exceptions from this rule. Considering a specific character of a capitalist country, the author stands for the constitutionality of the State partial financing the faith organizations social activity and for the exempting them from taxes. Whereas, the subsidizing the denominational school system seems to be unconstitutional, excluding some forms of material aid for a student. Simultaneously, he criticizes the Supreme Court judicature which finds a partial subsidizing of primary and secondary faith schools contrary to the Constitution, whereas this position is not applied to higher schools. Some analogies with the Supreme Court policy line concerning the racial segregation problem are pointed out by the author. Furthermore, the author evaluates his own suggested solutions from the point of view of the socialist constitutionalism. He creates his own theoretical model of the church and state separation institution and stresses the role of the principle of not granting any material aid to faith organizations. However, on the other hand, he tries to show that this ban cannot be interpreted in an absolute way, suggesting it should not be applied if it could violate the citizens’ conscience and worship clause. The article is closed with the summing-up of the religious freedom realization in the USA.